GAYA HIDUP FANATISME KOMUNITAS CYPHER ARMY MALANG - Ari Fijianti; Puspita Pebri Setiani; Muhammad Naharuddin Arsyad; Amanah Agustin; Ali Badar (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
The Malang Cypher Army Community is a social group of people formed because they have similarities and the same goals. This community is a place for BTS fans to gather and interact. The purpose of this research is to find out the fanatical lifestyle of the Cypher Army Malang community and consumerism about purchasing merchandise related to BTS. This research is qualitative by using descriptive analysis method. The results of the study show that community members are included in the indicators of fanaticism. Like, imitation, consumptive behavior, and obsession. Imitation is an attempt to intentionally imitate the actions of others, such as clothing styles, language styles and so on. Consumptive behavior, which is happening at this time, is that someone buys goods not because of their use but because of the prizes offered, the items purchased are trending, or buy goods because of certain logos or symbols. Obsession, which is the desire for something accompanied by desire and great effort. In consuming Korean goods, especially goods from BTS, there is often a difference in understanding in terms of wants and needs. In addition, there is often a shift in the use value of a product. This happens because the value of the symbol or sign attached to the item can show the identity of the user of the item.